2022
DOI: 10.1038/s41598-022-12869-z
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive detection of salivary SARS-CoV-2 IgG antibodies in individuals with natural and COVID-19 vaccine-induced immunity

Abstract: We assessed the feasibility of a highly sensitive immunoassay method based on single molecule array (Simoa) technology to detect IgG and IgA antibodies against SARS-CoV-2 spike protein receptor binding domain (RBD) in saliva from individuals with natural or vaccine-induced COVID-19 immunity. The performance of the method was compared to a laboratory-developed SARS-CoV-2 RBD total antibody enzyme-linked immunosorbent assay (ELISA). Paired serum and saliva specimens were collected from individuals (n = 40) prior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 43 publications
1
17
0
Order By: Relevance
“…[28][29][30] To overcome the challenge associated with low total IgG concentrations in saliva compared to blood some have resorted to concentrating saliva, either with or without additional accounting for salivary total IgG, which resulted in increased assay sensitivity but reduced specificity. 31 Despite the lower assay performance most groups found that blood SARS-CoV-2 IgG levels correlate well with salivary IgG levels 32 , however, such findings are often based on very small sample sizes. 31,33,34 Studies with larger sample sizes typically report less robust correlations between saliva and blood antibody levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[28][29][30] To overcome the challenge associated with low total IgG concentrations in saliva compared to blood some have resorted to concentrating saliva, either with or without additional accounting for salivary total IgG, which resulted in increased assay sensitivity but reduced specificity. 31 Despite the lower assay performance most groups found that blood SARS-CoV-2 IgG levels correlate well with salivary IgG levels 32 , however, such findings are often based on very small sample sizes. 31,33,34 Studies with larger sample sizes typically report less robust correlations between saliva and blood antibody levels.…”
Section: Discussionmentioning
confidence: 99%
“…31 Despite the lower assay performance most groups found that blood SARS-CoV-2 IgG levels correlate well with salivary IgG levels 32 , however, such findings are often based on very small sample sizes. 31,33,34 Studies with larger sample sizes typically report less robust correlations between saliva and blood antibody levels. 30,35 In the Ambulatory COVID-19 Study cohort nearly all participants had seroconverted by saliva IgG to SARS-CoV-2 two weeks post COVID-19 symptoms onset and SARS-CoV-2 IgG levels were stable for the duration of the study.…”
Section: Discussionmentioning
confidence: 99%
“…During the last 2 years, a great number of saliva-based sensor technologies for SARS-CoV-2related proteins, namely viral antigens or SARS-CoV-2 antibodies, have been reported. [5][6][7][8] The positive test for SARS-CoV-2related proteins rapidly identifies the infected individuals in situations where and when the RT-PCR test is not available. The clinical value of saliva-based protein sensors is extended to other infectious disease diagnostics (i.e., rapid tests for malaria), [9] personalized medicine (i.e., routine tests for chronic lung disease or heart disease), [10,11] and other medical conditions affecting millions of people (i.e., on-site tests for physiological stress detection, early-stage detection of cancer, etc.).…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, oral mucosal fluid (saliva) specimens are non-invasive, enable self-collection, and require less processing, reducing cost 14 . Multiple studies demonstrated that anti-S-protein IgG levels can be robustly measured in saliva specimens with high sensitivity and specificity from infected or vaccinated individuals, even though salivary Ab concentrations are 100-10,000-fold lower than in serum 15,16 . IgG titers for serum and saliva are strongly correlated, indicating they represent a surrogate for anti-S-protein IgG levels in serum 15,16 .…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies demonstrated that anti-S-protein IgG levels can be robustly measured in saliva specimens with high sensitivity and specificity from infected or vaccinated individuals, even though salivary Ab concentrations are 100-10,000-fold lower than in serum 15,16 . IgG titers for serum and saliva are strongly correlated, indicating they represent a surrogate for anti-S-protein IgG levels in serum 15,16 . In contrast, anti-S-protein IgA Abs are not reliably detected in saliva, although serum IgA titers increase in response to infection or vaccination and are consistently detected in specimens 16 .…”
Section: Introductionmentioning
confidence: 99%